2004
DOI: 10.1111/j.1365-2958.2004.04197.x
|View full text |Cite|
|
Sign up to set email alerts
|

Homologous recombination in Candida albicans: role of CaRad52p in DNA repair, integration of linear DNA fragments and telomere length

Abstract: SummaryChromosomal rearrangements are common in both clinical isolates and spontaneous mutants of Candida albicans . It appears that many of these rearrangements are caused by translocations around the major sequence repeat (MSR) that is present in all chromosomes except chromosome 3, suggesting that homologous recombination (HR) may play an important role in the survival of this organism. In order to gain information on these processes, we have cloned the homologue of RAD52 , which in Saccharomyces cerevisiae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
68
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(76 citation statements)
references
References 89 publications
8
68
0
Order By: Relevance
“…Miller & Sarachek (1974) concluded that C. albicans does not possess a photoreactivating enzyme. We searched the genome sequence of C. albicans for photolyase homologues and did not find any good candidates, in agreement with an earlier report of a BLAST search of the C. albicans genome (Ciudad et al, 2004). However, a photoreactivation activity could be masked by a very efficient NER pathway, which would be uncovered by the NER mutants.…”
Section: Susceptibility To Dna-damaging Agentssupporting
confidence: 66%
“…Miller & Sarachek (1974) concluded that C. albicans does not possess a photoreactivating enzyme. We searched the genome sequence of C. albicans for photolyase homologues and did not find any good candidates, in agreement with an earlier report of a BLAST search of the C. albicans genome (Ciudad et al, 2004). However, a photoreactivation activity could be masked by a very efficient NER pathway, which would be uncovered by the NER mutants.…”
Section: Susceptibility To Dna-damaging Agentssupporting
confidence: 66%
“…Two conserved proteins integral to homologous recombination in Saccharomyces cerevisiae and higher eukaryotes are Rad51p and Rad52p (Krogh and Symington, 2004). C. albicans Rad52p has also been shown to be critical for survival in the presence of DNA damaging agents such as MMS (Ciudad et al, 2004). Based on its homology to S. cerevisiae RAD51, orf19.3752 has been designated C. albicans RAD51, with a putative role in homologous recombination (candidagenome.org).…”
Section: Deletion Of Rad51 or Rad52 Results In Increased White-opaquementioning
confidence: 99%
“…In C. albicans, as in many fungi, DNA repair is often mediated through homologous recombination (Ciudad et al, 2004;Krogh and Symington, 2004). Two conserved proteins integral to homologous recombination in Saccharomyces cerevisiae and higher eukaryotes are Rad51p and Rad52p (Krogh and Symington, 2004).…”
Section: Deletion Of Rad51 or Rad52 Results In Increased White-opaquementioning
confidence: 99%
“…After incubation at 30°C for 72 h, the colony-forming units were determined as described previously (Ciudad et al, 2004).…”
Section: Dna Damage Assaymentioning
confidence: 99%